Find the sum of all the integral values of a such that the quadratic expression ( x + a ) ( x + 1 9 9 1 ) + 1 can be factored as ( x + b ) ( x + c ) where b and c are integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are given the expression ( x + a ) ( x + 1 9 9 1 ) + 1 .We need to factor it in the form ( x + b ) ( x + c ) where b,c are integers.
So we can equate both the equations,
( x + a ) ( x + 1 9 9 1 ) + 1 = ( x + b ) ( x + c )
or, x 2 + ( 1 9 9 1 + a ) x + ( 1 9 9 1 a + 1 ) = x 2 + ( b + c ) x + b c
or, ( 1 9 9 1 + a ) x + ( 1 9 9 1 a + 1 ) = ( b + c ) x + b c ................................................................ (1)
Comparing the co-efficients of x & x 0 we get the following two equations :
b + c = 1 9 9 1 + a .................................................. (2)
b c = 1 9 9 1 a + 1 ....................................................(3)
By (3) - (2) ,
b c − b − c = 1 9 9 0 a − 1 9 9 0
or, ( b − 1 ) ( c − 1 ) = 1 9 9 0 a − 1 9 8 9
since (1990,1989) = 1, so a = 1 9 8 9 which leads to ( b − 1 ) ( c − 1 ) = 1 9 8 9 2 & thus b & c have integral values 1990 respectively.
Again by (2) + (3) ,
b c + b + c = 1 9 9 2 a + 1 9 9 2
or, ( b + 1 ) ( c + 1 ) = 1 9 9 2 a + 1 9 9 3
Again since (1992,1993) = 1 , So a = 1 9 9 3 which leads to ( b + 1 ) ( c + 1 ) = 1 9 9 3 2 & thus b & c have the values 1992 respectively.
The sum of the possible values of a is : 1 9 9 3 + 1 9 8 9 = 3 9 8 2 .
Did the exact same....
Given:(x+a)(x+1991)+1. If the expression is factored as (x+b)(x+c), -b and -c are the roots of the above polynomial. Therefore, (-b+a)(-b+1991)=-1. Either a-b=1,1991-b=-1 or a-b=-1,1991-b=1 (as b and c are integers). Solving, we get a=1989 or a=1993. Required sum=1989+1993=3982.
Problem Loading...
Note Loading...
Set Loading...
( x + a ) ( x + 1 9 9 1 ) + 1 = ( x + b ) ( x + c ) Put x = − b to get ( a − b ) ( 1 9 9 1 − b ) = − 1 and knowing the fact that product of two integers is − 1 iff they are 1 , − 1 . Setting I . a − b = − 1 , 1 9 9 1 − b = 1 gives a = 1 9 8 9 .
Similarly setting I I . a − b = 1 , 1 9 9 1 − b = − 1 gives a = 1 9 9 3 . Hence sum = 1 9 8 9 + 1 9 9 3 = 3 9 8 2 .